Antioxidant and Anti-cancer effects of crude extracts from (Vitis vinifera L.) leaves on melanoma cells (SK-Mel and A375) - Selma, Ferhi; Chahinez, Taib; Salim, Gasmi; Sakina, Zerizer; Guy, D’hallewin (Emirates Journal of Food and Agriculture, 2021)
This study aimed to estimated total phenol, the antioxidant and antiproliferative activities of crude extract derived from grape leaves (Vitis vinifera. L.). Total phenol of grape leaves (Vitis vinifera. L.) was extracted using aqueous and methanol solvent and dosed with Folin-Ciocalteu using spectrophotometry. The antioxidant activity was estimated by spectrophotometry in the existence of the DPPH radical, when the antiproliferative activity was evaluated by using MTT test on two melanoma cells (A375 and SK-MEL) as compared to the effect of Cisplatinum. Results showed that extracts of grape leaves (Vitis vinifera. L.) were rich in total phenols. Indeed, the extracts exhibited an antioxidant activity, when 1.98 mg/mL of methanol and aqueous crude extracts could inhibit 90.20 % and 77.78 % of DPPH* radical respectively. The proliferation of Melanoma cells A375 and SK-MEL is decreased with increasing concentration of water and methanolic extracts (1.136, 2.27, and 4.54 mg/mL) included in the culture throughout 72 h. Results offered that extract from grape leaves (Vitis vinifera. L.) characterize with biological effect compounds such as phenols, with promise antioxidant activity, revealing an antiproliferative effect impact on A375 and SK-MEL malignant tumor cells compete with the synthetic molecule Cisplatinium.